Pelatihan Pemanfaatan Wordwall dan Quizizz untuk Pembelajaran IPA: Pemberdayaan Guru SDN Tambelang 1 Kabupaten Probolinggo - Afib Rulyansah; Rizqi Putri Nourma Budiarti; Emy Yunita Rahma Pratiwi; Sri Hartatik; Pance Mariati; Jauharotur Rihlah (Indonesia Berdaya, 2022)
Because of the Covid-19 epidemic, the learning method in primary schools has shifted from conventional learning to virtual learning, which is more effective. One of the challenges elementary school instructors face is the usage of virtual learning apps that are appealing to pupils. Virtual learning applications are becoming more popular. This service activity is a training session for teachers at SDN Tambelang 1 in Probolinggo Regency on how to utilize the Quizziz and Wordwall programs in the classroom to enhance learning. The participants in this activity will be 11 teachers who will be service partners with the organization. The Zoom platform is used for all of the activities that take place online. The exercise is divided into two stages: the first stage involves the presentation of content and practice with the Quizizz program, and the second stage involves the presentation of material and practice with the Wordwall application, respectively. Techniques for gathering information with surveys or questionnaires. The average participant answer was utilized in the data analysis. The replies of participants revealed that instructors developed knowledge and abilities in the use of the Quizizz and Wordwall programs, which was a good outcome. The inability of the internet network to function properly is a stumbling block in this endeavour.  Abstrak: Karena wabah Covid-19, metode pembelajaran di sekolah dasar telah bergeser dari pembelajaran konvensional ke pembelajaran virtual yang lebih efektif. Salah satu tantangan yang dihadapi guru sekolah dasar adalah penggunaan aplikasi pembelajaran virtual yang menarik bagi siswa. Aplikasi pembelajaran virtual menjadi lebih populer. Kegiatan pengabdian ini merupakan sesi pelatihan bagi para guru di SDN Tambelang 1 Kabupaten Probolinggo tentang bagaimana memanfaatkan program Quizziz dan Wordwall di dalam kelas untuk meningkatkan pembelajaran. Peserta dalam kegiatan ini adalah 11 orang guru yang akan menjadi mitra pengabdian organisasi. Platform Zoom digunakan untuk semua aktivitas yang dilakukan secara online. Latihan dibagi menjadi dua tahap: tahap pertama melibatkan penyajian konten dan praktik dengan program Quizizz, dan tahap kedua melibatkan penyajian materi dan praktik dengan aplikasi Wordwall masing-masing. Teknik pengumpulan informasi dengan survei atau kuesioner. Rata-rata jawaban partisipan digunakan dalam analisis data. Balasan peserta mengungkapkan bahwa guru mengembangkan pengetahuan dan kemampuan dalam penggunaan program Quizizz dan Wordwall, yang merupakan hasil yang baik. Ketidakmampuan jaringan internet untuk berfungsi dengan baik menjadi kendala dalam upaya ini.